2020
DOI: 10.5455/medarh.2020.74.19-23
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Self-reported Respiratory Symptoms, Asthma and use of Asthma Medication Among Young Adolescents from Southeast Kosovo

Abstract: Introduction: Asthma is a chronic inflammatory airway disease characterized by episodes of airway narrowing leading to manifestations of symptoms such as wheeze, shortness of breath, chest tightness and cough, that may resolve spontaneously or following treatment. Aim: The aim of this paper was to present the collected data related to the prevalence of self-reported respiratory symptoms, asthma, and use of asthma medication among school children aged 13-14 years from the city of Gjilan, a municipality located … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Preliminary data from few other global centers have shown mixed results regarding time trends in the prevalence of current wheeze. [20][21][22] Data from a single center in Mexico showed a 7.9% increase in the prevalence of current wheeze in both age groups compared with ISAAC phase III. 20 On the other hand, the GAN phase I study conducted in Bangkok suggests a similar prevalence of current wheeze in the younger age group and slightly lower prevalence in the older age group when compared with the ISAAC phase III.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary data from few other global centers have shown mixed results regarding time trends in the prevalence of current wheeze. [20][21][22] Data from a single center in Mexico showed a 7.9% increase in the prevalence of current wheeze in both age groups compared with ISAAC phase III. 20 On the other hand, the GAN phase I study conducted in Bangkok suggests a similar prevalence of current wheeze in the younger age group and slightly lower prevalence in the older age group when compared with the ISAAC phase III.…”
Section: Discussionmentioning
confidence: 99%
“…The world total data showed a significant decline in current wheeze, with both increase and decrease noted as per individual centre. Preliminary data from few other global centres have shown mixed results regarding time trends in the prevalence of current wheeze [ 20 22 ]. Data from a single centre in Mexico showed a 7.9% increase in the prevalence of current wheeze in both age groups compared with ISAAC Phase III [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…8 Hence, early diagnosis and treatment of allergy (generally centered on allergycauses identification/reduction/elimination, allergen immunotherapy, symptomatic treatment, and antihistamines) 1,4,5,7,9,10 are important to prevent its consequences. Unfortunately, some studies showed that many people with allergic diseases did not receive physician treatment (for instance 20% to 70% for asthma) 1,[11][12][13][14] and have impaired quality of life. 15 Some doctors hesitate to diagnose asthma and some parents/children deny it.…”
mentioning
confidence: 99%
“…15 Some doctors hesitate to diagnose asthma and some parents/children deny it. 11 The socioeconomic costs of allergy and its consequences are much higher than allergy-treatment cost. 1,4 During adolescence, emotional brain development (involving changes in limbic and cognitive control circuitry) is particularly pronounced, while the demand for self-regulation across various emotional and social situations would be highest.…”
mentioning
confidence: 99%
See 1 more Smart Citation